Students’ interest in physical education learning: Analysis of internal and external factors - Kurniawan, Rama; Kurniawan, Ari Wibowo; Wijaya, Dimas (Journal Sport Area, 2021)
In physical education, learning interests are required so that the intentions of this meant learning are well accomplished. This research is aimed to find out the descriptions of students’ interest factors when attending physical education learning at State Senior High School 2 Malang. This study employed a quantitative descriptive research design through survey methods. In order to obtain the research data, a questionnaire was employed as the research instrument with 329 students as the research subjects. After the data were collected, they were analyzed by using a type of descriptive statistical analysis. The results of this research indicated that students’ interest in learning physical education of X class students in State Senior High School 2 Malang both of internal and external factors were classified as high categories. Internal factors influenced students’ interests more during physical education learning compared to external factors. Overall, the activity factor and feeling of pleasure are the most influential factors for their involvement in physical education learning. Understanding that, students and teachers are suggested to look at intervening toward each above factors as an effort to improve their interest in learning.